2017
DOI: 10.1186/s13104-017-2834-z
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to iron supplements among women receiving antenatal care at Mulago National Referral Hospital, Uganda-cross-sectional study

Abstract: BackgroundAntenatal iron supplementation is a cost effective way of reducing iron deficiency anaemia among pregnant women in resource limited countries like Uganda. Poor adherence to iron supplements has limited its effectiveness in reducing maternal anaemia as evidenced by the high burden of iron deficiency anemia in Sub-saharan Africa. The aim of this study was to determine the level of and factors associated with adherence to iron supplementation among women attending antenatal clinic at Mulago National Ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
41
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 18 publications
18
41
2
2
Order By: Relevance
“…The result of this study revealed that 44% of pregnant women were adherent to IFAS which is consistent with a study done at Egypt (41%), Misha district (39%) and Bahir Dar (42%) [24–26]. On the other side, it is higher than the study done at Uganda (12%), Kenya (33%), Goba, Southeast Ethiopia (18%) and Mecha district (20%) [17,18,27,28]. The possible reasons might be the study setting and time which means our study was Hospital-based and recent whereas their studies were community-based.…”
Section: Discussionsupporting
confidence: 89%
“…The result of this study revealed that 44% of pregnant women were adherent to IFAS which is consistent with a study done at Egypt (41%), Misha district (39%) and Bahir Dar (42%) [24–26]. On the other side, it is higher than the study done at Uganda (12%), Kenya (33%), Goba, Southeast Ethiopia (18%) and Mecha district (20%) [17,18,27,28]. The possible reasons might be the study setting and time which means our study was Hospital-based and recent whereas their studies were community-based.…”
Section: Discussionsupporting
confidence: 89%
“…These findings corroborated with studies conducted in Mizan-Aman, Ethiopia, and Pakistan [28,32]. Studies conducted in Uganda, Pakistan, and South Africa found that less supply of IFAS had low adherence to IFAS [24,32,33]. Other studies conducted in Ismailia government and Assela town-Ethiopia reported that crowding of tablets was associated with the low adherence to supplementation [34,35].…”
Section: International Journal Of Reproductive Medicinesupporting
confidence: 81%
“…Similarly, studies conducted in Kiambu, Kenya (32.7%), and Amhara, Western Ethiopia (20.4%), also found the low adherence to IFAS among pregnant women [19,20]. Also, adherence to IFAS was modestly higher compared to the studies conducted in Eastern Kenya (18.3%), Uganda (12%), Norway (16%), and Northern Tanzania (16.1%) [21][22][23][24] and lower compared to studies conducted in Senegal (51%), Kathmandu-Nepal (73.2%), Tamil Nadu-India (60.6%), and Mizan-Aman-Ethiopia (70.6%) [25][26][27][28]. Some of the probable reasons of inconsistency might be a different study subject, sociodemographic characteristics, locality, follow-up and reminding mechanism, knowledge of IFAS, and qualities of health services offered in the health facilities including counseling on its benefits, the average number of IFAS recommended during pregnancy, and belief on the use of IFAS.…”
Section: Discussionmentioning
confidence: 85%
“…A er duplication was removed, 99 articles remained of which 78 were excluded as a result of not ful lling to our inclusion criteria by reviewing for their titles and abstracts. en 21 full-text articles were accessed based on inclusion criteria [16,17,[35][36][37][38][39][40][41][42][43][44][45]. Finally, 12 studies which ful lled the inclusion criteria [16][17][18][19][20][21][22][23][24][25][26][27] were included in the meta-analysis ( Figure 1).…”
Section: Characterstics Of Reviewedmentioning
confidence: 99%